2020
DOI: 10.1186/s13244-019-0834-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings and classification of the common and uncommon male breast diseases

Abstract: Male breast hosts various pathological conditions just like "female breast." However, histo-anatomical diversities with female breast lead to many differences regarding the frequency and presentation of diseases, the radiologic appearance of lesions, the diagnostic algorithm, and malignity features. Radiological modalities may play an important role in evaluating male breast lesions. Although some imaging findings are non-specific, having knowledge of certain imaging characteristics and radiologic patterns is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…In contrast, the preponderance of T secretion in men favors involution of the ducts, while TDLU maturation is absent. 26 As a result, the male breast, compared with the female, may be considered as a rudimentary structure consisting mainly of subcutaneous adipose tissue, vestigial ductal tissue devoid of mammary lobules, and a small nipple-areolar complex. In addition, in the male breast, Cooper ligaments are absent, whereas pectoral muscles are more prominent 27 (Figure 2).…”
Section: Anatomy: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the preponderance of T secretion in men favors involution of the ducts, while TDLU maturation is absent. 26 As a result, the male breast, compared with the female, may be considered as a rudimentary structure consisting mainly of subcutaneous adipose tissue, vestigial ductal tissue devoid of mammary lobules, and a small nipple-areolar complex. In addition, in the male breast, Cooper ligaments are absent, whereas pectoral muscles are more prominent 27 (Figure 2).…”
Section: Anatomy: Histologymentioning
confidence: 99%
“…On the other hand, fibrous GM expands in the surrounding tissues adapting a "spider leg" appearance and the echogenicity of the lesions increases as fibrosis develops (Figure 5C). 26,71 In color-Doppler US imaging, the florid form is commonly associated with increased vascularity, representing an inflammatory process of recent onset.…”
Section: Ure 5bmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in many studies that the spread of COVID-19 is very fast. [16][17][18] In addition, it has been reported that a patient with COVID-19 can infect an average of 2.6 people. 7 It was determined that the students who found COVID-19 positive in one of his acquaintances had low life satisfaction (Table 2).…”
Section: Life Satisfaction Scalementioning
confidence: 99%
“…In most cases, it represents the result of an unbalanced androgen to estrogen ratio (8). Apart from gynecomastia, male breast lesions can be grouped based on histopathological type and behavior, into two main categories as "benign" and "malignant" (9,10).…”
mentioning
confidence: 99%